SGLT2 inhibitors for alleviating heart failure through non-hypoglycemic mechanisms - Chen, Ya-ru; Zhu, Fang-yuan; Zhou, Rong (Frontiers in Cardiovascular Medicine, 2024)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors afford significant cardiovascular benefits to patients with diabetes mellitus and heart failure. Three large randomized clinical trials (EMPAREG-Outcomes, DECLARE-TIMI58, and DAPA-HF) have shown that SGLT2 inhibitors prevent cardiovascular events and reduce the risk of death and hospital admission resulting from heart failure. Patients without type 2 diabetes mellitus (T2DM) also experience a similar degree of cardiovascular benefit as those with T2DM do. SGLT2 inhibitors could improve cardiac function through potential non-hypoglycemic mechanisms, including the reduction of the circulatory volume load, regulation of energy metabolism, maintenance of ion homeostasis, alleviation of inflammation and oxidative stress, and direct inhibition of cardiac SGLT1 receptors and antimyocardial fibrosis. This article reviews the mechanism through which SGLT2 inhibitors prevent/alleviate heart failure through non-hypoglycemic pathways, to support their use for the treatment of heart failure in non-T2DM patients.